Heads up games as a tool to promote participation in EFL students in the classroom - Castrillo Villanueva, María Marcela | Rayo Castellón, Orlando Alexander | Toledo Morales, Denis | Alemán, Jaime Roberto Alemán Jaime Roberto (Nicaragua | MANAGUA UNAN, Managua, 2021)
This research is based on heads up game as tool to promote participation in EFL students in the classroom,The purpose of this research is to explore, increase and finally to explore the heads up game as a tool increase the participation.To demonstrate that the implementation of games in the classrooms helps the teaching and learning in the English language and also the increase of the participation of the children of the Federicko Kuhn 3A school. Obtaining the information, five observations were made during the English’s class, with the intention of understand how the teacher, applies games in the classroom and how it promotes children's participation through such games and how the student is motivated to participate voluntarily and in a safe environment in the teaching of the English language.Furthermore, an interview to the teacher was made to know about the implementation of the games and that the games are a way to be able to teach in a proactive way and that it has a great influence in the teaching of a language and that the participation in the children tends to have a process of knowledge in a positive way. Finally, a survey was applied to 10 students of 32 from 3rd grade, in order to show up in which way they were affected by no implementation on game in the classroom that carried out to having a great participation in the English class
Seminario-(Licenciados en Ciencias de la educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua
Keywords: Ingles-Enseñanza | Juegos educativos | Inglés-Técnicas de enseñanza | Inglés-Seminarios-2021